Upgrading of Wash Oil through Reduction of Nitrogen-Containing Compounds - Su Jin Kim (MDPI AG, 2021)
As part of improving the quality of wash oil, the reduction of three kinds of nitrogen-containing compounds (NCs), including quinoline (QU), iso-quinoline (IQU), and indole (IN), found in wash oil was examined by liquid–liquid equilibrium extraction. The wash oil and an aqueous solution of formamide were used as the raw material and the solvent, respectively. Increasing the volume fraction of water in the solvent in the initial state (yw,0) resulted in a decrease in the distribution coefficients of each NC, while inversely, the selectivity of each NC in reference to 2-methylnaphthalene increased. The selectivity ranges of QU, IQU and IN at yw,0 = 0.05~0.3 were 19~57, 19~56 and 50~79, respectively. Through five stages of equilibrium extraction performed under the condition of yw,0 = 0.05, the concentrations of QU and IQU contained in the raffinate oil recovered at the fifth stage were reduced by about 69% and 65% compared to those contained in the wash oil. The concentration of IN in particular, a useful compound in the chemical industry, which is a raw material for pharmaceuticals, dyes, and fragrances, was reduced by 93.4% through a five-stage extraction operation. The formamide extraction method of this study was highly efficient in reducing the NC present in the wash oil, showing the feasibility of this method.